Quality changes of fresh cut cantaloupe (Cucumis melo L. var Reticulatus cv. Glamour) in different types of polypropylene packaging - Kamaruddin, Syahidah; Shamsudin, Rosnah; Mohd Adzahan, Noranizan; Othman, Zaulia; Ahmedov, Anvarjon (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Consumers today prefer to purchase ready-to-eat, fresh-cut fruit that is readily available at the markets and retailers. They generally select the fresh-cut fruit base on the quality, freshness, nutrition and safety. The effects of packaging condition on fresh-cut Cantaloupe were studied during 18 days of storage at 2°C and 87% RH. Fresh-cut Cantaloupe pieces were packed in a Polypropylene (PP) container. As a control, the container was cover with lid without film, while Sample 1 (S1) was sealed only by a 40 μm PP film and Sample 2 (S2) was sealed with a 40 μm PP film and then adding the lid cover. Changes in colour, firmness Total Soluble Solids (TSS), pH, Titratable Acidity (TA) and Total Plate Count (TPC) were evaluated over time. During storage, it was found that the firmness significantly decreased from day 0 until day in all packaging conditions. Color parameters Luminosity (L*) and Chromaticity (C) were significantly change at the significance level of 95% (p<0.05) while hue angle (hab) were not significant (p<0.05) change for all types of packaging. Meanwhile, pH, Titratable Acidity (TA) and Total Plate Count (TPC) were significantly changed over time at the significance level of 95% (p<0.05). The fresh cut cantaloupe packed with the control method showed better appearance and quality as compared to the other treatments after 18 days of storage. These results suggest that the PP container with a lid cover only (control) is suitable to be used for fresh cut cantaloupe during the first 18 days of storage at 2°C.